Ovidiu Papadima – o evocare - Teodor Vârgolici (Revista de Istorie și Teorie Literară)
Ovidiu Papadima truly deserved his place between The Creators and Their World, because he transmited to the world their message, by his wide and remarkable book named like that. By the time, Ovidiu Papadima’s great scientific prestige had been recognized by the authorities, so he was allowed to prepare scholars for the PhD title. Theodor Vargolici was between the first of them. O.P. has decided for him to have as the main theme, a book about Dimitire Bolintineanu. O.P. was respected as a folklorist, literary critic and literary historian. O.P. became famous as an writer in 1942, after he published the volume A Romanian Vision of the World. In an article, Petru Comarnescu wrote that A Romanian Vision of the World is “ the most lightning and signifying initiation in the Romanian Weltanshaung”. Studying the Romanian folklore, O.P. has declared that: “The way the people are seeing the World is organic Christian”.